2018
DOI: 10.1016/j.ijnurstu.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Discharge education delivered to general surgical patients in their management of recovery post discharge: A systematic mixed studies review

Abstract: The quality of discharge education has an influence on patient participation in their management of care post discharge. Assessing patients' preparedness for discharge is an essential component of discharge planning process. The presentation, timing and frequency of discharge education was important in the delivery of information. Tailored education reflecting the learning needs of patients using multiple media delivered in varying doses enhanced patients' overall knowledge for successful management of recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 47 publications
3
63
2
4
Order By: Relevance
“…Hospital discharge is a key transition phase for patients and caregivers. Assessing patients’ readiness for discharge is an essential component of the discharge planning process 238. Detailed education should be provided to the patient and caregiver.…”
Section: Resultsmentioning
confidence: 99%
“…Hospital discharge is a key transition phase for patients and caregivers. Assessing patients’ readiness for discharge is an essential component of the discharge planning process 238. Detailed education should be provided to the patient and caregiver.…”
Section: Resultsmentioning
confidence: 99%
“…Involving patients in the decision making with their plan of care on discharge has been associated with improved patient outcomes (Uldry, Schäfer, Saadi, Rousson, & Demartines, 2013). Although there has been a focus on using a patient-centred approach in the delivery of discharge education, a review identified factors such as insufficient staffing, lack of time and nurses not considering discharge education as their primary role as reasons for not engaging patients in discharge education (Kang, Gillespie, Tobiano, and Chaboyer (2018).…”
Section: Introductionmentioning
confidence: 99%
“…High risk patients for post-operative complications should be identified and may need a post-operative follow-up. Adequate discharge education of patients about the normal post-operative course and complications enhances the participation in their healthcare management [ 16 ]. Additionally, mismatch in expectancy of patient and doctor in different healthcare domains could lead to overrating low value healthcare [ 6 ].…”
Section: Discussionmentioning
confidence: 99%